Neutralisation of Heparan Sulphate and Low Molecular Weight Heparin by Protamine - Hubbard, A R; Jennings, C A (Thrombosis and Haemostasis, 1985)
The neutralisation by protamine sulphate (PS) of heparan sulphate (HS), a low molecular weight heparin (LMWH), and a reference preparation of unfractionated heparin (UH), was studied by activated partial thromboplastin time (APTT) and anti-Xa clotting assays. UH was most easily neutralised in the APTT assay by PS (on a weight for weight basis), followed by LMWH and HS. The neutralisation of APTT activity by PS closely followed the loss of activity in the anti-Xa clotting assay, when plasma was used as the source of At III. When the anti-Xa clotting assay was carried out using purified At III in place of plasma, HS and LMWH were neutralised by much lower amounts of PS and resembled UH neutralisation more closely. Resistance of HS anti-Xa activity to PS neutralisation decreased with increasing plasma dilution. The presence of bovine albumin with purified At III concentrate increased the resistance of HS to PS neutralisation. It is concluded that PS binding to UH, HS and LMWH is probably related more to their degree of sulphation than molecular weight and that non-specific interactions between PS and plasma proteins inhibit the binding of PS to HS and LMWH.
Keywords: Heparan sulphate; Low molecular weight heparin; Protamine sulphate; APTT; Anti-Xa activity